Preserving Culture and Heritage of the Yoruba of Southwest Nigeria: An Ethnographic Study of the Twin Figure (Ere Ibeji) (SCHOLARS: Journal of Arts & Humanities, 2022)
Ere Ibeji is the carved wooden figure used to commemorate the death of twin(s) among the Yoruba people of Southwest, Nigeria. Existing literature focuses on myth, sacred and artistic values of this traditional wood carving while issues of protection and preservation of its tangible as well as intangible belief system are gradually fading out. This study aimed at sustaining the twin’s figuring carving tradition, which seems to be winding out due to civilization. The study examined available data surrounding twins’ birth, thereby advocating the preservation of the surviving ere ibejis. The findings of the study show a reasonable number of ere ibejis that have been taken outside Nigeria while others are in the national museums. The study recommends the retrieval of the ones taken abroad, the use of improved conservation methods in the museums as well as the promotion of cultural heritage management in Nigeria.